Pengaruh Dividend Payment dan Leverage terhadap Cash Holding pada Perusahaan Building Construction Bursa Efek Indonesia - Sri Winarsih Ramadana; Agustina (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2022)
The purpose of this study was to examine the effect of dividend payments and leverage, either partially or simultaneously, on cash holding at the Indonesia Stock Exchange building construction company in 2017-2021. The data analysis method in this study uses multiple linear regression (multiple regression) to predict the effect of the independent variables. The population in this study were 15 companies listed on the Indonesia Stock Exchange building construction company in 2017-2021. Then 11 samples were obtained with 5 years of observation and 55 observations according to the criteria. The results showed that dividend payments and leverage, either simultaneously or partially, had an effect on cash holding in the construction of company buildings listed on the Indonesia Stock Exchange for that period.